CIRCULAR ECONOMY DRIVEN INNOVATIONS WITHIN BUSINESS MODELS OF RURAL SMEs - Uvarova, Inga; Atstaja, Dzintra; Vitola, Alise (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The competitiveness of rural SMEs is low due to economic inefficiency and the lack of innovations. The main challenges faced by rural SMEs are the limited scale, the distance form larger sales markets, R&D and business support institutions, and the lack of innovative spirit. The circular and bio-economies are shaping the rural SMEs towards the environmentally friendly and eco-efficient production, the minimization of the generation of waste and less use of natural resources. This potential of the adoption of new business models within rural SMEs is not fully observed.The aim of this research is to analyse the opportunities of rural SMEs in introducing the innovative business models driven by the circular economy. This research explores the innovative business models of rural SMEs that transform the environmental challenges in business opportunities and keep a balance with the growing consumption needs. The results of the research are of both theoretical and practical value, providing recommendations for facilitation of innovative business models within rural SMEs. The research methods: desk research, statistical analysis, a grounded theory approach, case study, primary data gathering through seven focus groups with more than 200 stakeholders from six European countries.